(untitled) (American Journal of Multidisciplinary Research and Innovation, 2022)
This study was conducted to evaluate the culture potentiality and growth performance of Spirulina (Spirulina platensis) in supernatant digested rotten guava (DRG) in replacement of Kosaric Medium (KM). The Spirulina was inoculated to grow in digested rotten guava media (DRGM) (treatments) with the addition of 9.0 g/L NaHCO3 and micronutrients and KM for a period of 14 days. The cell weight of spirulina was attained a maximum of 12.43±0.20 mg/L (dry wt. basis) in KM followed by 0.818 ± 0.003, 0.815 ± 0.0015 and 0.809± 0.0012 mg/L in supernatant of 60 (T1), 20 (T2) and 40% DRGM (T3), respectively on the 10th day of culture. The cell weight of spirulina grown in these media had highly significant (P<0.01) correlation with the chlorophyll a content (r = 0.746) and total biomass (r = 0.742) of Spirulina. The results showed that the growth performance of spirulina in supernatant of 60% DRGM was significantly (P<0.01) higher than that of spirulina grown in supernatant of 20% and 40% DRGM. The physico-chemical parameters viz. light intensity (2748 to 2768 lux/m2/s), temperature (19.0 to 22.2°C), pH (8.1 to 10.6), alkalinity (1522 to 2698 mg/L), nitrate-N (1.25 to 3.64 mg/L) and phosphate-P (11.30 to 55.40 mg/L) were within optimum level during the culture period. The results showed that, the different concentration of digested rotten guava (20%, 40%, 60%) has potential to increase the growth rate of Spirulina. Therefore, the DRG medium may be commercially used for mass culture of Spirulina platensis.